Recollection and Confession : the Heidelberg catechism as a site of memory in the Dutch Reformed Church, 1862-1963 - Van Tonder, Helene (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.